Hubungan Kemampuan Berkomunikasi Guru dengan Motivasi Belajar Siswa di Sekolah Dasar - NurHasanah NurHasanah; muh. idris jafar; adnan,K Adnan,K; Kamaruddin Hasan (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
The problem in this study is that the teacher's communication skills affect student responses in receiving learning materials so that students have different motivations. This research is a correlational quantitative research that aims to determine the relationship between teacher communication skills and student learning motivation at SD Country 24 Macanang. The research data were obtained by distributing questionnaires to students. The results showed that there was a significant relationship between teacher communication skills and student learning motivation at SD country 24 Macanang with a Â valueof (3.1962) greater (>) Â value (1.6741) which means H0 is rejected and H1 is accepted. Based on the results of the study, it can be concluded that the teacher's communication skills will have an impact on students' learning motivation. So the better the teacher's communication skills, the better the students' learning motivation. From these conclusions, the impact resulting from this study is known that a good teacher's communication skills will increase students' learning motivation..Â